SUSPENSIVE EFFECT OF AN APPEAL IN ADMINISTRATIVE AND TAX PROCEEDINGS - Dimić, Suzana; Петровић, Невена; Бојанић, Бојан (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2025)
In this paper, the authors analyze the suspensive effect of an appeal in the course of resolving an administrative matter, and the suspensive effect of an appeal as a regular legal remedy in a tax administrative procedure. In addition to the analysis of the suspensive effect of an appeal in administrative procedure, the authors examine the suspensive effect of a complaint in an administrative dispute, starting from the fact that the procedure for resolving an administrative matter, in practice, often does not end before the administrative authorities in the original administrative procedure. Rather, the procedure upon appeal continues before the court, thus integrating the systemically connected resolution of the administrative matter within the administrative-judicial procedure. As a rule, an appeal as a regular legal remedy in a tax proceeding does not have a suspensive effect. The reason for this is the protection of the financial interest of the state, given that taxes and other duties for financing public needs are determined in tax proceedings. Considering that an appeal as a regular legal remedy in a legal proceeding was introduced with the aim of protecting legality and the rights of the parties, there is an impression that the need for efficiency of the fiscal system takes precedence over these goals. In this paper, the authors aim to address several tasks: 1) to establish whether the current form of the suspensive effect of an appeal in administrative or tax procedure contributes to the effectiveness of the aforesaid legal remedy; 2) to assess the quality of the legal regulation of the suspensive effect of a complaint in an administrative dispute proceeding; and 3) to offer solutions to these issues de lege ferenda based on the obtained research results.